The German Administrative Jurisdiction in European Comparative Law - Sydow, Gernot (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
This study is devoted to analysing the structural decisions related to the administrative jurisdiction in Germany in comparison with other European countries. It focuses, in particular, on the institutional structure of the administrative jurisdiction and the functions associated with it to it. Different understanding of the scope of the administrative jurisdiction pre-determine how individual regulations of administrative procedural law are designed, for example, regulations concerning access to courts and the judicial powers of the administrative courts. Therefore, the article aims to demonstrate – from a comparative legal perspective – the processes of mutual interaction, namely how the structural decisions made about the administrative jurisdiction have been received, and to highlight the different developmental trends characteristic of individual countries.